Osteopontin acts as a negative regulator of autophagy accelerating lipid accumulation during the development of nonalcoholic fatty liver disease - Min Tang; Yan Jiang; Haoyu Jia; Bhuvanesh Kinish Patpur; Bo Yang; Jing Li; Changqing Yang (Artificial Cells, Nanomedicine, and Biotechnology)
Accumulating evidence links osteopontin (OPN), a pro-fibrogenic extracellular matrix protein, to the pathogenesis of non-alcoholic fatty liver disease (NAFLD). In this study, liver tissues isolated from non-alcoholic steatohepatitis (NASH) patients expressed higher OPN than those of controls. However, the exact mechanism(s) for this phenomenon is yet to be clarified. Autophagy is the natural, regulated degradation and recycling of a cell's dysfunctional components, in order to maintain homeostasis. Increasing evidence supports that autophagy can constitute an effective Defence mechanism against NAFLD conditions. Herein, we constructed NAFLD mice model by high-fat (HF) and methionine-choline-deficient (MCD) diet and found that OPN is upregulated in livers of NAFLD mice. Besides, secreted OPN inhibited autophagosome-lysosome fusion via binding with its receptors integrin αVβ3 and αVβ5 in HepG2 cells supplemented with free fatty acids (FFA) and the livers of NAFLD mice. Silencing of OPN attenuated autophagy impairment and reduced lipid accumulation, while supplementation of OPN exhibited the opposite effect. Furthermore, treatment with anti-OPN Ab significantly attenuated steatosis as well as autophagy impairment in the liver. Our findings indicated that OPN plays a vital role in the pathogenesis of the development of NAFLD via autophagy impairment, which might represent a potential new therapeutic target for the treatment of NAFLD.